1988
DOI: 10.1007/bf01420770
|View full text |Cite
|
Sign up to set email alerts
|

Gelled emulsions with a high water content

Abstract: The structure of a gel containing 99 % water, 0.5 % of a nonionic surfactant and 0.5 % of a hydrocarbon was investigated by analysis of its equilibrium phases and their state of dispersion by liquid helium freeze fracture electron microscopy.The gel consisted of aqueous droplets of micron size separated by a thin membrane of a lamellar liquid crystal and a W/O microemulsion with droplets varying between 200 and 1000 A in diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…It is known that HIPREs can form in the water (O/W) and oil (W/O) rich region under certain conditions [2,[9][10][11]. Due to their characteristic features such as high volume fraction of the internal phase, high viscosity, and transparency, they are also referred to as gel emulsions [1,3,12,13]. Rheological properties of HIPREs were also studied and found that range from viscoelastic to elastic nature depending on the system composition and temperature [6,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that HIPREs can form in the water (O/W) and oil (W/O) rich region under certain conditions [2,[9][10][11]. Due to their characteristic features such as high volume fraction of the internal phase, high viscosity, and transparency, they are also referred to as gel emulsions [1,3,12,13]. Rheological properties of HIPREs were also studied and found that range from viscoelastic to elastic nature depending on the system composition and temperature [6,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Highly concentrated or high internal phase ratio emulsions (HIPREs) have been the objects of many studies for several years [1][2][3][4][5][6][7][8]. It is known that HIPREs can form in the water (O/W) and oil (W/O) rich region under certain conditions [2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…At such a high concentration, the surfactant-water mixture most likely involves liquid crystal phases and only in exceptional cases consists solely of micellar or molecular liquid solutions. However, except for the related contributions by Solans [1,[30][31][32][33], no systematic efforts have been made to identify liquid crystal structures in these systems and to discuss their relevance for the inversion process. Finally, the truly fundamental question still remains as to the necessity of the presence of additional liquid crystal phases for inversion to occur as well as for the subsequent formation of emulsions of high internal phase volume [30].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the vast divergence between the rheological properties of the liquid crystals and the emulsion liquids, the effect by the liquid crystals on the emulsion rheological properties is expected to be of pronounced interest and Solans was the first to realize the consequences of such effects [10] in the first of a long series of articles on gel emulsions. [11] A few attempts to more fundamental contributions have later been made and the contributions by Masalova et al [12] as well as Alam et al [13,14] deserve mentioning.These efforts have as expected been expanded into investigations into more applied fields of which personal care products [15][16][17] and pharmaceuticals [18,19] are the most noteworthy, but even to more exotic emulsions [20] have been included.…”
Section: Introductionmentioning
confidence: 99%